2003
DOI: 10.1046/j.1365-3091.2003.00551.x
|View full text |Cite
|
Sign up to set email alerts
|

Threshold for particle entrainment into suspension

Abstract: Laboratory observations regarding the limit conditions for particle entrainment into suspension are presented. A high‐speed video system was used to investigate conditions for the entrainment of sediment particles and glass beads lying over a smooth boundary as well as over a rough bed. The results extend experimental conditions of previous studies towards finer particle sizes. A criterion for the limit of entrainment into suspension is proposed which is a function of the ratio between the flow shear velocity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
150
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(176 citation statements)
references
References 43 publications
(57 reference statements)
10
150
2
Order By: Relevance
“…Overall, in the time series significant variability and intermittency both in Reynolds stress (u , w ) and sediment resuspension (backscatter) was also revealed. Such intermittent nature of u w was expected and observed previously in the laboratory (Grass, 1974;Sumer and Oguz, 1978;Sumer and Deigaard, 1981;Niño et al, 2003;Schmeeckle, 2015) and in the field (Heathershaw and Thorne, 1985;Drake et al, 1988;Soulsby et al, 1994;Kularatne andPattiaratchi, 2008 andYuan et al, 2009). In more detail, the time series of the AMCV run showed 28 major resuspension events (Fig.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Overall, in the time series significant variability and intermittency both in Reynolds stress (u , w ) and sediment resuspension (backscatter) was also revealed. Such intermittent nature of u w was expected and observed previously in the laboratory (Grass, 1974;Sumer and Oguz, 1978;Sumer and Deigaard, 1981;Niño et al, 2003;Schmeeckle, 2015) and in the field (Heathershaw and Thorne, 1985;Drake et al, 1988;Soulsby et al, 1994;Kularatne andPattiaratchi, 2008 andYuan et al, 2009). In more detail, the time series of the AMCV run showed 28 major resuspension events (Fig.…”
Section: Resultssupporting
confidence: 82%
“…Although Lavelle and Mofjeld (1987) previously reviewed the concept of critical stress for the initial motion of non-cohesive sediment beds under turbulent flow conditions suggesting the non-existence of true threshold in the movement of sediment, their conclusions were based on photographic observations employed in conjunction with current measurements to infer sediment thresholds in the field. Likewise, the work from Niño and Garcia (1996) and Niño et al (2003) identified such instantaneous events from high-speed videos, which limit the number of captured and analysed events. We examined the influence of turbulent coherent structures on sediment resuspension for flows both above and below the measured mean critical resuspension velocity over a flat sandy bed using widely used acoustic instruments.…”
Section: Discussionmentioning
confidence: 99%
“…The d 50 particle represents the median size of the sediment substrate and a lower bracket for estimating sediment mobility. The d 85 particle represents an upper threshold for estimating armor destabilization and wholesale substrate mobility (Parker & Klingeman, 1982;Nino et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Sediment travels as bed load once the critical shear velocity (u * c ), is exceeded and as long as w s =u à sk ≥ 2:5 [Niño et al, 2003], where w s is the particle fall velocity calculated using the methods of Dietrich [1982]. The development of a measurable suspended sediment concentration profile typically occurs when w s =u à sk ≤1 [Bagnold, 1966].…”
Section: Mode Of Transportmentioning
confidence: 99%